Esempio ed esemplarità in Kant, tra etica minima ed etica massima - Da Re, Antonio (Filosofia Morale/Moral Philosophy, 2022)
The essay examines Kant’s position on moral exemplarism, through the interpretative categories of minimal ethics and maximal ethics. Kant criticises the moral model of actual people, especially when it is associated with a morality of excellence. However, in some other works, he appreciates the exemplary nature of ideal figures (the Stoic sage and especially Jesus), who should be followed (Nachfolge), rather than imitated. Finally, in this regard, it is relevant Kant’s valorisation of practical judgement, where he uses some examples to account for different ethical instances, such as those related to perfect and imperfect duties.